Implementation of the Independent Curriculum in Fiqh Subjects at MAN 1 East Lampung - Siti Nurhidayah; Ikhwan Aziz Q; Rina Mida Hayati (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to analyze the implementation of the independent curriculum which is focused on the implementation of the Pancasila (P5) student profile strengthening program in the context of fiqh learning at MAN 1 East Lampung. The P5 program is designed to shape students' personalities based on the principles of Pancasila. MAN 1 East Lampung has implemented an independent curriculum since 2020. Basic religion in this madrasah supports the implementation of the P5 independent curriculum at MAN 1 East Lampung. This research was conducted using a qualitative method with data collection techniques consisting of observation, interviews with curriculum officials, fiqh subject teachers, and several grade 10 students.The results of the study show that the P5 Program is recognized as an important part of education in madrasas. At MAN 1 East Lampung, the implementation of P5 in the context of Fiqh learning has gone very well. Students not only understand the concepts taught, but are also able to implement them in real life, both in the madrasah environment and at home. This success is supported by qualified teacher competence in managing project-based learning and the availability of very adequate school facilities. With this support, the implementation of the Independent Curriculum, especially in the P5 Program, can run optimally and have a positive impact on the formation of students' character.